2016
DOI: 10.1074/jbc.a111.287433
|View full text |Cite
|
Sign up to set email alerts
|

IKBKE protein activates Akt independent of phosphatidylinositol 3-kinase/PDK1/mTORC2 and the pleckstrin homology domain to sustain malignant transformation.

Abstract: The same data were used to represent different experimental conditions. Specifically, the Myc-IKBKE immunoblot from Fig. 4B was reused as the Myc-IKBKE immunoblot in Fig. 4C. The IKBKE immunoblot from Ikbke Ϫ/Ϫ MEFs treated with EGF was reused in the IKBKE panel from Ikbke Ϫ/Ϫ MEFs treated with insulin in supplemental Fig. S5A. In supplemental Fig. S5B, the pAkt-T308 immunoblot from Ikbke Ϫ/Ϫ MEFs treated with glucose was reused in the pAkt-T308 panel from wild type MEFs treated with amino acid. The authors st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…In the previous study with proline, PRODH was shown to increase Akt phosphorylation (Ser473) and phosphorylation of the Akt downstream target, FoxO3 [Natarajan et al, ]. Phosphorylation of FoxO3 by Akt prevents activation of pro‐apoptotic genes thus promoting cell survival [Guo et al, ]. In this study, inhibition of Akt abolished phosphorylation of FoxO3 and the protective effect of pipecolate.…”
Section: Discussionsupporting
confidence: 56%
“…In the previous study with proline, PRODH was shown to increase Akt phosphorylation (Ser473) and phosphorylation of the Akt downstream target, FoxO3 [Natarajan et al, ]. Phosphorylation of FoxO3 by Akt prevents activation of pro‐apoptotic genes thus promoting cell survival [Guo et al, ]. In this study, inhibition of Akt abolished phosphorylation of FoxO3 and the protective effect of pipecolate.…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, we did not observe this association in OED samples (Figure ), which leads us to suggest that the activation of AKT in these injuries could happen through a mechanism that does not involve the classic mode of AKT activation, that is, through its prior activation at the membrane. Recent studies have demonstrated that other kinases can interact with AKT and induce cellular transformation without requiring the PI3K signaling pathway (Mahajan et al , ; Guo et al , ; Joung et al , ; Xie et al , ; Mahajan and Mahajan, ). Ser/Thr kinase I‐κ‐B kinase epsilon (Iκκε) has the ability to activate AKT regardless of the PH domain and without requiring PI3K, mTORC2, or PDK1 (Guo et al , ; Xie et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that other kinases can interact with AKT and induce cellular transformation without requiring the PI3K signaling pathway (Mahajan et al , ; Guo et al , ; Joung et al , ; Xie et al , ; Mahajan and Mahajan, ). Ser/Thr kinase I‐κ‐B kinase epsilon (Iκκε) has the ability to activate AKT regardless of the PH domain and without requiring PI3K, mTORC2, or PDK1 (Guo et al , ; Xie et al , ). The non‐receptor tyrosine kinase Ack I (activated CDC42‐associated kinase 1) is able to recruit and activate AKT by inducing the phosphorylation of Tyr176 residue without necessitating PI3K activity (Mahajan et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, phosphorylation of FOXO3a by IKBKE does not rely on the Akt pathway (70). Recent research suggests that IKBKE, which activates Akt, can directly phosphorylate Akt at Thr308 and Ser473, therefore, IKBKE regulates FOXO3a activity directly, and also regulates the activity of FOXO3 indirectly via the Akt pathway (71). In addition, it has been demonstrated that phosphorylation of FOXO3a caused by IKBKE decreases the expression of IFN-β to participate in the regulation of the immune response (72).…”
Section: Iκb Kinase (Iκk)mentioning
confidence: 99%